2020
DOI: 10.1186/s13019-020-01315-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of both internal thoracic arteries for coronary revascularization increases the estimate of post-operative lower limb ischemia in patients with peripheral artery disease

Abstract: Background Patients with a history of peripheral arterial disease (PAD) undergoing coronary artery bypass grafting (CABG) exhibit higher rates of complications. There are conflicting data on the survival benefits for bilateral thoracic artery (BITA) grafting compared with left internal thoracic artery (LITA) CABG in patients with PAD. The aim of the study was to explore the influence of the use of BITA grafts vs. LITA for CABG on post-operative acute lower limb ischemia (ALLI) and main post-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(83 reference statements)
0
1
0
1
Order By: Relevance
“…Several studies have reported lower extremity ischemia in patients in whom the internal thoracic artery was harvested for coronary artery grafting. 3 , 4 , 5 , 6 Lower extremity ischemia is a known serious complication of internal thoracic artery harvesting 7 ; studies have reported that lower extremity bypass surgery should be performed before harvesting the internal thoracic artery to prevent the aforementioned complication. 8 , 9 , 10 To our knowledge, only a single report has described lower extremity ischemia secondary to harvesting the deep inferior epigastric artery, which was used as a free rectus abdominis myocutaneous flap, 11 and lower extremity ischemia is not a known complication of inferior epigastric artery harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported lower extremity ischemia in patients in whom the internal thoracic artery was harvested for coronary artery grafting. 3 , 4 , 5 , 6 Lower extremity ischemia is a known serious complication of internal thoracic artery harvesting 7 ; studies have reported that lower extremity bypass surgery should be performed before harvesting the internal thoracic artery to prevent the aforementioned complication. 8 , 9 , 10 To our knowledge, only a single report has described lower extremity ischemia secondary to harvesting the deep inferior epigastric artery, which was used as a free rectus abdominis myocutaneous flap, 11 and lower extremity ischemia is not a known complication of inferior epigastric artery harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Аналіз Micali et al продемонстрував, що у пацієнтів із ЗПА після вінцевого шунтування на 14 % вище ризик виникнення гострої ішемії нижніх кінцівок у разі бімамарного шунтування при порівнянні з використанням лише лівої внутрішньої грудної артерії (p < 0,001) [36].…”
unclassified